Binding of imidazole, 1-methylimidazole and 4-nitroimidazole to yeast cytochrome c peroxidase (CcP) and the distal histidine mutant, CcP(H52L) - Erman, James E. (Biochim Biophys Acta, 2015)
Imidazole, 1-methylimidazole and 4-nitroimidazole bind to yeast cytochrome c peroxidase (yCcP) with apparent equilibrium dissociation constants ([Formula: see text]) of 3.3 ± 0.4, 0.85 ± 0.11, and ~0.2 M, respectively, at pH 7. This is the weakest imidazole binding to a heme protein reported to date and it is about 120 times weaker than imidazole binding to metmyoglobin. Spectroscopic changes associated with imidazole and 1-methylimidazole binding to yCcP suggest partial ionization of bound imidazole to imidazolate. The pK(a) for ionization of bound imidazole is estimated to be 7.4 ± 0.2, about 7 units lower than that of free imidazole and about 3 units lower than imidazole bound to metmyoglobin. Equilibrium binding of imidazole to CcP(H52L) is biphasic with low- and high-affinity phases having [Formula: see text] values of 9.5 ± 4.5 and 0.13 ± 0.04 M, respectively. CcP(H52L) binding of 1-methylimidazole is monophasic with an affinity similar to those of yCcP and rCcP. Binding of 1-methylimidazole to rCcP is associated with two kinetic phases, the initial binding complete within 10 s, followed by a process that is consistent with 1-methylimidazole binding to a cavity created by movement of Trp-191 from the interior of the protein to the surface. Both the equilibrium binding and kinetics of 1-methylimidazole binding to yCcP are pH dependent. yCcP has a four-fold increase in 1-methylimidazole binding affinity on decreasing the pH from 7.5 to 4.0, an observation that is unique among the many studies on binding of imidazole and imidazole derivatives to heme proteins.